Golkar Party's Strategy in Winning the 2019 Legislative Elections: Case Study - Kadir Jailani, Abdul; Alyas, Alyas; Parawu, Hafiz Elfiansyah; Akbar, Andi (Borong Newinera Publisher, 2026)
This study aims to analyze the Golkar Party's strategy in winning the 2019 Legislative Election (Case Study: Golkar Party of South Sulawesi Province). The method used is descriptive qualitative with a phenomenological approach. The data analysis technique is through data reduction, data presentation and verification or drawing conclusions. The results of the study indicate that planning plays an important role in the scope because it determines and at the same time provides direction to the goals to be achieved. Meanwhile, the implementation of the strategy, namely the organization must set annual targets, create policies, motivate legislative candidates, and allocate resources can be implemented. So that in the evaluation can review the external and internal factors that emerged in the first stage, measure performance and take corrective actions or improvements when discrepancies arise later. The supporting factors of the Golkar party strategy are the influential and widely known regional leaders in South Sulawesi so that they can increase the attractiveness of voters to the party and prepare the legislative candidates who are prepared to be the best cadres who are encouraged, but the inhibiting factor is that the coordination between the legislative candidates is not good so that it causes internal divisions so that the target votes are almost the same as the votes being fought over so that it does not result in an increase in votes, apart from that because of the strength or popularity of competing parties and other candidates who may be more attractive to voters.